HUMAN-INDUCED CHANGES IN PROPERTIES OF SOLONETZ SOILS UNDER CONDITIONS OF FOREST AMELIORATION IN PRE-ERGENI PLAIN OF KALMYKIA - A. F. Novikova; M. V. Konyushkova; A. A. Kontoboitseva (Бюллетень Почвенного института им. В.В. Докучаева, 2012)
Under study are changes in morphological, chemical and physicochemical properties of solonetz soils resulted from prolonged anthropogenic effects (more than 55 years) under conditions of forest amelioration in Pre-Ergeni plain of Kalmykia. The current status of anthropogenically-modified solonetz soils is conditioned by dissolution-salinization processes taken place in soils due to irrigation, being after that affected by forest amelioration and the aftereffect of deep meliorative tillages to a lesser extent. As a result of forestation the soils became moistened thanks to snow accumulation, the evaporation decreased thanks to shading of the soil surface. The root system improved the water permeability and produced CO2 in order to increase the dissolution of carbonates in soil. Dissolution of the upper 50-65 cm layer of anthropogenically-modified soilonetz soils remains for a long period of time. General trend in the development of solonetz soils under forest plantations is directed to dissolving and decreasing the content of absorbed sodium in plough and subsurface horizons.